Repeated occurrences of marine anoxia under high atmospheric O 2 and icehouse conditions - Jitao Chen; Shihan Li; Shuang Zhang; Terry Isson; Tais W. Dahl; Noah J. Planavsky; Feifei Zhang; Xiang-dong Wang; Shu-zhong Shen; Isabel P. Montañez (Proceedings of the National Academy of Sciences, 2025)
The Late Paleozoic Ice Age (~340 to 260 Ma) occurred under peak atmospheric O 2 (1.2 to 1.7 PIAL, pre-industrial atmospheric levels) for Earth history and CO 2 concentrations comparable to those of the preindustrial to that anticipated for our near future. The evolution of the marine redox landscape under these conditions remains largely unexplored, reflecting that oceanic anoxia has long been considered characteristic of carbon cycle perturbation during greenhouse times. Despite elevated O 2 , a 10 5 -y period of CO 2 -forced oceanic anoxia was recently identified, but whether this short-term interval of widespread oceanic anoxia was anomalous during this paleo-ice age is unexplored. Here, we investigate these issues by building a high-resolution record of carbonate uranium isotopes (δ 238 U carb ) from an open-marine succession in South China that permits us to reconstruct the global marine redox evolution through the deep glacial interval (310 to 290 Ma) of near peak O 2 . Our data reveal repeated, short-term decreases in δ 238 U carb coincident with negative C isotopic excursions and rises in paleo-CO 2 , all superimposed on a longer-term rise in δ 238 U carb . A carbon–phosphorus–uranium biogeochemical model coupled with Bayesian inversion is employed to quantitatively explore the interplay between marine anoxia, carbon cycling, and climate evolution during this paleo-glacial period. Although our results indicate that protracted, enhanced organic carbon burial can account for the long-term O 2 increase, seafloor oxygenation, and overall low CO 2 , episodic pulses of C emissions had the potential to drive recurring short-term periods of marine anoxia (with 4 to 12% of seafloor anoxia) despite up to 1.7 times higher atmospheric O 2 than present day.